Menghidupkan Kembali Masa Lalu: Sebuah Studi tentang Bagaimana Generasi Z Memahami dan Mengadopsi Tren Fashion Vintage - Pradana, Dhanar; Ratuannisa, Tyar (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
This research project is primarily dedicated to comprehension of individuals' perspectives on vintage fashion styles. In the contemporary era, vintage fashion has not only emerged as a substantial trend within the fashion industry but has also captured the interest of numerous individuals who are drawn to clothing and accessories reflecting elements from bygone eras. Employing a quantitative research methodology and utilizing the semantic differential approach, the study endeavors to quantify and understand consumers' perceptions of products embodying vintage styles. Furthermore, the investigation seeks to discern the various factors that contribute to shaping individuals' perceptions of vintage fashion, including the influences of prevailing fashion trends and cultural elements.The significance of acquiring an in-depth understanding of the intricate nature of perceptions surrounding vintage fashion within the broader fashion landscape holds considerable potential for elucidating how individuals engage with the historical dimensions of fashion. Despite the scarcity of research focus on this particular phenomenon, this study is prompted by the imperative to scrutinize the factors that impact consumer interest and comprehension of fashion trends in Indonesia, employing constructed perceptions as a framework. Consequently, the research aims to address and bridge existing knowledge gaps, aspiring to provide a more profound and nuanced understanding of the role that vintage fashion plays in the Indonesian fashion industry and its consequential impact on individual perceptions. In conclusion, Generation Z exhibits a well-rounded knowledge of vintagestyle fashion, understanding distinctive characteristics like silhouettes, colors, and era-specific motifs. They possess awareness of specific years, recognize brands, and differentiate vintage fashion from new products.